A Fixed Flow is More Effective than Titrated Flow during Bubble Nasal CPAP for Respiratory Distress in Preterm Neonates - Murki, Srinivas; Das, Ratan Kumar; Sharma, Deepak; Kumar, Praveen (Frontiers in Pediatrics, 2015)
Background: The clinical effects of a pre-fixed flow of air-oxygen versus a flow titrated according to visible bubbling are not well understood. Objective: To compare the effects of a fixed flow (5 L/min) and titrated flow ( flow just enough to ensure bubbling ) at different set pressures on delivered intra-prong pressure, gas exchange and clinical parameters in preterm infants on bubble CPAP for respiratory distress. Methods: Preterm infants less than 35 weeks gestation on bubble CPAP and less than 96 h of age, were enrolled in this cross over study. They were subjected to 30 minute periods of titrated flow and fixed flow. At the end of both epochs, gas flow rate, set pressure, FiO2, SpO2, Silverman retraction score, respiratory rate , abdominal girth, and blood gases were recorded. The delivered intra-prong pressure was measured by an electronic manometer. Results: Sixty nine recordings were made in 54 infants. For each of the set CPAP pressures (4, 5 and 6 cm H2O), the mean delivered pressure with a fixed flow of 5 L/min was higher than that delivered by the titrated flow. During the fixed flow epoch, the delivered pressure was closer to and higher than the set pressure resulting in higher PaO2 and lower PaCO2 as compared to titrated flow epoch. In the titrated flow period, the delivered pressure was consistently lower than the set pressure. Conclusion: In preterm infants on bubble CPAP with set pressures of 4 to 6 cm H2O, a fixed flow of 5 L/min is more effective than a flow titrated to ensure adequate visible bubbling. It achieves higher delivered pressures, better oxygenation and ventilation.